Perusakan Lingkungan Hidup di Indonesia: Efektivitas Regulasi Lingkungan Hidup Indonesia (Perspektif Sosiologi Hukum) - Adhitya, Claudio Ricky; Nainggolan, Kezia Elvira; Sinaga, Emi Juliana; Susanti, Ester; Halan, Vincentia Cordialia (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2025)
The enjoyment and utilization of the environment is the right of the people of Indonesia as guaranteed under the 1945 Constitution of the Republic of Indonesia. Therefore, the Government of the Republic of Indonesia issued Law Number 32 of 2009 on the Protection and Management of Environment (Environment Law) as the embodiment of the rights of the people of Indonesia to enjoy and utilize the environment. As time flew by, the execution of the Environment Law encountered issues due to violations toward said law, such as environment destruction in the form of land clearing by means of burning. Since the issuance of the Environment Law, violations have been carried out by several parties, including but not limited to law enforcers, business owners, and the people of Indonesia themselves. This research focuses on the prohibition toward environment destruction in the form of land clearing by means of burning as well as the reasons and the sociological factors affecting the effectiveness of the implementation of the environmental laws. This research is aimed to identify the main factors affecting the failure of the enforcement of the Environment Law as well as other environmental laws and regulations. In addressing the said issues, this research utilizes the normative legal research methodology towards secondary data consisting of environmental laws, analyzed using the qualitative data analysis methodology. In conclusion, ineffectiveness of Indonesian environment laws are due to weakness in its enforcement, ambiguity in its norms, and failure of Indonesian legal culture to adhere to its legal principles.